The Discovery and Excavation of a Human Burial from the Mini-athiliya Shell Midden in Southern Sri Lanka. (10th November 2014) - Kulatilake, Samanti; Perera, Nimal; Deraniyagala, Siran U.; Perera, Jude
Several shell middens of coastal Sri Lanka indicate human occupation in the mid-Holocene and are recognized as being of prime importance in the archaeological narrative of the island. A salvage archaeology operation conducted at the Mini-athiliya shell midden in the Southern Province of Sri Lanka, yielded ancient human remains associated with stone implements and culturally modified faunal remains. The main objective of this rescue operation was to mitigate the destruction to this archaeological site. We report the excavation strategy and dating of this mid-Holocene shell midden, while focusing on the discovery and extraction of a complete human burial that had not been disturbed by the shell mining activity at the site. This excavation is intended to serve as a precursor to systematic investigation of the coastal shell middens of southern Sri Lanka.